IMPLEMENTASI PENDIDIKAN ETIKA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MEMBENTUK KARAKTER MORAL SISWA SEKOLAH DASAR - Rini Maldianci Teuf; Fadil Mas’ud; Gupuh Rahayu; Ngurah Dharma Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the implementation of ethical education in Civic Education learning to form moral character of elementary school students. The background of this research is the increasing concern about moral degradation among students, marked by deviant behavior and decreased sense of social responsibility. This study uses a qualitative descriptive method with a literature study approach, where data is collected from various literatures related to ethical education and character. The results of the analysis show that ethical education integrated into the curriculum and supported by teacher modeling is able to foster moral values such as honesty, responsibility, and empathy in students. The conclusion of this study emphasizes that ethical education in schools needs to be designed systematically and continuously in order to form strong moral character relevant to the challenges of the times, especially through Civic Education learning which becomes the main vehicle for moral value formation.